An Instantaneous Minimum Input Energy Control Strategy for Isolation Systems With Co-Varying Stiffness and Damping - Leilei Xia; Dehong Wu; Lu Chen; Jingjing Li (IEEE Access)
The seismic isolation stiffness and damping of magnetorheological elastomer (MRE) isolation bearings can adapt instantly to seismic load variations which can provide more intelligent seismic protection for engineering structures. The stiffness and damping change simultaneously following a defined functional relationship. For such systems, an instantaneous minimum input energy (IMIE) control strategy is proposed. This algorithm explicitly establishes the functional relationship between damping and stiffness, converting the optimization problem into a single-variable search for optimal stiffness while automatically determining the corresponding optimal damping. The IMIE strategy operates through total minimization of seismic-induced kinetic energy transmission to the structure and isolation system’s actuation energy consumption during each discrete time interval. A bridge isolation system with MRE isolation bearings is controlled by proposed IMIE algorithm. The control effects under different seismic excitation are compared with passive control, Linear Quadratic Regulation (LQR) control and fuzzy control method. The results demonstrate that the IMIE algorithm effectively mitigates structural responses and exhibits distinct advantages in reducing input energy and MRE bearing displacements. It provides a new control thought and method for the engineering application of hybrid isolation systems.